Hak-hak Perempuan dalam Tafsīr Firdaws al-Na‘īm bi Tawḍīḥ Ma‘ānī Āyāt al-Qur’ān al-Karīm Karya KH. Thoifur ‘Ali Wafa - Hasanah, Uswatun (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2019)
This article strives for elaborating Thoifur Ali Wafa’s thoughts and his views on women’s rights in his Firdaws al-Na‘īm bi Tawḍīḥ Ma‘ānī Āyāt al-Qur’ān al-Karīm. His work discusses Qur’anic verses, which deals with women and their rights. Considering that Thoifur has been a Muslim scholar who born and live in Sumenep Madura whose people believe in superiority of men upon women, the issue is then undeniably interesting to discuss. It seems that Thoifur, through his work, attempts to reveal religious understanding which tends to be gender biased. He insists to obliterate patriarchal culture and discrimination against women as a result of irresponsibly fault social construction to the understanding of religious texts. Based on his interpretation of verse 21 surah al-Rūm, verse 232 surah al-Baqarah, verse 195 surah Āl ‘Imrān, verse 38 surah al-Mā’idah, verse 34 surah al-Nisā’, verse 187 surah al-Baqarah, verse 228 surah al-Baqarah, verse 19 surah al-Nisā’, verse 229 surah al-Baqarah, verse 36 surah al-Nisā’, verse 15 surah al-Aḥqāf, verse 71 surah al-Tawbah, verse 12 surah al-Mumtaḥanah, and verse 34 surah al-Nisā’, Thoifur argues that women possess a number of rights within both domestic and public spheres.